The Effectiveness of Canva as an Interactive Learning Media for the Qur'an and Hadith at the PAI Study Program at Ahmad Dahlan University - Adelia Astriani; Muh. Alif Kurniawan (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Canva is a web-based graphic design platform that is increasingly popular among individuals, professionals, and in education. This study aims to evaluate the effectiveness of Canva as an interactive learning medium in teaching the Qur'an and Hadith, as well as to see its impact on student interaction and understanding, and find solutions to improve its effectiveness in the Islamic Religious Education Study Program. The method used is qualitative with a descriptive approach, implemented in September, and involving Islamic Religious Education students and lecturers as data sources. Data collection was carried out through observation, interviews, documentation, and interpretation of user behavior and perceptions regarding the effectiveness of Canva. The results of the study indicate that Canva is effective in improving the quality of learning, with the ability to present interesting and interactive materials, which successfully attract attention and increase student motivation. In addition, Canva's collaborative features, such as digital whiteboards, strengthen interactions between students and lecturers, as well as between students, creating a dynamic learning atmosphere. However, there are several obstacles that must be overcome to improve its effectiveness. The study recommends the implementation of a planned strategy and institutional support, including training for lecturers and students and socialization of the benefits of Canva. Overall, Canva has the potential to create an inclusive and adaptive learning environment in the digital age, while helping students develop the digital skills needed to face future challenges. Therefore, the use of Canva in education needs to be continuously encouraged to provide maximum benefits for all parties involved.